2011
DOI: 10.1007/s00421-011-2183-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of near infrared spectroscopy (NIRS) for measuring forearm oxygenation during incremental handgrip exercise

Abstract: The purpose of this study was to test the reliability of a new handgrip exercise protocol measuring forearm oxygenation in 20 healthy subjects on two occasions. The retest took place 48 h later and at the same time of the day. The incremental exercise consisted of 2 min steps of cyclic handgrip contraction (1/2 Hz) separated by 1 min of recovery. The exercise started at 20% MVC, was increased with 10% MVC each step and was performed until exhaustion (69.5 and 73% MVC). Near infrared spectroscopy (NIRS) was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
48
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 13 publications
(24 reference statements)
3
48
1
2
Order By: Relevance
“…The current investigation suggests that the inter-test reliability of NIRS during multi-joint resistance exercise is lower than reported in previous investigations using isokinetic and isometric exercise (Celie et al, 2012;Kell et al, 2004;Pereira et al, 2005;Tanimoto and Ishii, 2006). While great attention was paid to standardize experimental conditions between exercise trials, several factors may have contributed to the day-to-day variability observed.…”
Section: Reliability Of Nirs Measurescontrasting
confidence: 60%
See 2 more Smart Citations
“…The current investigation suggests that the inter-test reliability of NIRS during multi-joint resistance exercise is lower than reported in previous investigations using isokinetic and isometric exercise (Celie et al, 2012;Kell et al, 2004;Pereira et al, 2005;Tanimoto and Ishii, 2006). While great attention was paid to standardize experimental conditions between exercise trials, several factors may have contributed to the day-to-day variability observed.…”
Section: Reliability Of Nirs Measurescontrasting
confidence: 60%
“…While previous research has established the test-retest reliability of NIRS to monitor muscle oxygenation status during various exercise protocols (Celie et al, 2012;Kell et al, 2004;Pereira et al, 2005;Tanimoto and Ishii, 2006), this research is the first to assess the reproducibility of NIRS during isotonic multi-joint resistance exercise. The current data demonstrate that at most intensities and set volumes, HbO 2min and HHb max values display acceptable intra-test reliability.…”
Section: Reliability Of Nirs Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…24,28 The NIRS device, placed at the forearm, noninvasively, monitored changes in muscle oxygenation, by measuring micromolar (µmol/L) relative changes from baseline for oxygenated, deoxygenated, and total hemoglobin. 29,30 NIRS also assessed the tissue saturation index (TSI), as an absolute parameter for muscle oxygenation. Muscle microvascular function was assessed during reactive hyperemia, as previously described.…”
mentioning
confidence: 99%
“…Within the skeletal muscle, light is absorbed by hemoglobin in small arterioles, capillaries, and venules of the microcirculation, causing changes in oxygenated, deoxygenated, and total hemoglobin NIRS signals, and provides information on the balance of oxygen delivery and utilization. 29,31,37 The NIRS signals arise predominantly from capillaries as these microvessels compose the largest portion of vascular volume in skeletal muscle (>90%), and the NIRS light can only pass through vessels <1 mm. 25,31,37,38 Thus, NIRS signals mainly reflect changes in capillary (hemoglobin related) oxygen levels and provide information on the microcirculation.…”
mentioning
confidence: 99%